2012
DOI: 10.1143/jjap.51.07gf19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cortical Bone Layer on Fast and Slow Waves in Cancellous Bone: Investigations Using Stratified Models

Abstract: We study inflation and reheating in a brane world model derived from type IIA string theory. This particular set-up is based on a model of string mediated supersymmetry breaking. The inflaton is one of the transverse scalars of a D4-brane which has one of its spatial dimensions stretched between two NS5branes, so that it is effectively three-dimensional. This D4-brane is attracted to a D6-brane that is separated from the 5-branes by a fixed amount. The potential of the transverse scalar due to the D4/D6 intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
(82 reference statements)
1
4
0
Order By: Relevance
“…The fast wave arrival time is also getting quicker when the cortical thickness increases. The findings of this study align well with previous research, which also reported the presence of both fast and slow waves even when the cancellous bone models are surrounded by cortical layers 13 . The observation also aligns with previous works, where typically fast wave has lower amplitude than slow wave [6][7][8][9][10][11] .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The fast wave arrival time is also getting quicker when the cortical thickness increases. The findings of this study align well with previous research, which also reported the presence of both fast and slow waves even when the cancellous bone models are surrounded by cortical layers 13 . The observation also aligns with previous works, where typically fast wave has lower amplitude than slow wave [6][7][8][9][10][11] .…”
Section: Resultssupporting
confidence: 92%
“…Not only that, most human bone structures are also covered with cortical bone which is a denser type of bone than cancellous bone. The existence of these bones may affect the two modes wave 13 . Therefore, it is necessary to investigate the utilization of the fast and slow waves in the human cancellous bone structure, which is predominantly covered by cortical bone.…”
Section: Introductionmentioning
confidence: 99%
“…The confirmation of the two-wave phenomenon under the condition in which cancellous bone is sealed with cortical bone, as reported by Mizuno et al (Mizuno et al, 2011a;Mizuno et al, 2011b) and Hosokawa and Nagatani (2012), encouraged us to apply this interesting phenomenon to a practical application. However, because the two waves sometimes overlap each other, depending on the conditions of the specimen, it can be difficult to distinguish their distinct features.…”
Section: Introductionmentioning
confidence: 52%
“…13) Moreover, by using ultrasonic microscopy, the acoustic characteristics of heart and liver tissues have been measured, and correlations between histopathological changes and changes in the speed of sound and attenuations have been revealed. [14][15][16][17] There are many reports on tissue characterization by ultrasound, [18][19][20][21][22][23][24][25] and those results show the basics of the structural simulation of tissues, 26,27) quantitative analyses of tissues, 28,29) and further practical diagnostic systems. Thus far, findings in biological tissues obtained by heating using ultrasonic diagnostic equipment have been reported; 30,31) however, analyses of the relationship between the heat denaturation and acoustic properties of biological tissues are not yet satisfactory.…”
Section: Ultrasonic Microscopymentioning
confidence: 99%